Optic Disc Vascularization in Glaucoma: Value of Spectral-Domain Optical Coherence Tomography Angiography - Pierre-Maxime Lévêque; Pierre Zéboulon; Emmanuelle Brasnu; Christophe Baudouin; Antoine Labbé (Journal of Ophthalmology)
Purpose. To detect changes in optic nerve head (ONH) vascularization in glaucoma patients using spectral-domain OCT angiography (OCT-A). Material and Method. Fifty glaucoma patients and 30 normal subjects were evaluated with OCT-A (AngioVue®, Optovue). The total ONH vessel density and temporal disc vessel density were measured. Clinical data, visual field (VF) parameters, and spectral-domain OCT evaluation (RNFL: retinal nerve fiber layer thickness, GCC: ganglion cell complex thickness, and rim area) were recorded for glaucoma patients. Correlations among total and temporal ONH vessel density and structural and VF parameters were analyzed. Results. In the glaucoma group, total and temporal ONH vessel density were reduced by 24.7% (0.412 versus 0.547; p<0.0001) and 22.88% (0.364 versus 0.472; p=0.001), respectively, as compared with the control group. Univariate analysis showed significant correlation between rim area (mm2) and temporal ONH vessel density (r=0.623; p<0.0001) and total ONH vessel density (r=0.609; p<0.0001). Significant correlations were found between temporal and total ONH vessel density and RNFL, GCC, VF mean deviation, and visual field index. Conclusion. In glaucoma patients OCT-A might detect reduced ONH blood vessel density that is associated with structural and functional glaucomatous damage. OCT-A might become a useful tool for the evaluation of ONH microcirculation changes in glaucoma.